Bipolarons rule the short-range terahertz conductivity in electrochemically doped P3HT. Issue 1 (14th December 2021) - Tsokkou, Demetra; Cavassin, Priscila; Rebetez, Gonzague; Banerji, Natalie
Abstract : In situ terahertz spectroscopy on electrochemically doped P3HT reveals the impact of polarons and bipolarons on the short-range conductivity. Abstract : Doping of organic semiconductor films enhances their conductivity for applications in organic electronics, thermoelectrics and bioelectronics. However, much remains to be learnt about the properties of the conductive charges in order to optimize the design of the materials. Electrochemical doping is not only the fundamental mechanism in organic electrochemical transistors (OECTs), used in biomedical sensors, but it also represents an ideal playground for fundamental studies. Benefits of investigating doping mechanisms via electrochemistry include controllable doping levels, reversibility and high achievable carrier densities. We introduced here a new technique, applying in situ terahertz (THz) spectroscopy directly to an electrochemically doped polymer in combination with spectro-electrochemistry and chronoamperometry. We evaluate the intrinsic short-range transport properties of the polymer (without the effects of long-range disorder, grain boundaries and contacts), while precisely tuning the doping level via the applied oxidation voltage. Analysis of the complex THz conductivity reveals both the mobility and density of the charges. We find that polarons and bipolarons need to co-exist in an optimal ratio to reach high THz conductivity (∼300 S cm −1 ) and mobility (∼7 cm 2 V −1 s −1 ) of P3HT in aqueous KPF6 electrolyte. In this regime, charge mobility increases and a high fraction of injected charges (up to 25%) participates in the transport via mixed-valence hopping. We also show significantly higher conductivity in electrochemically doped P3HT with respect to co-processed molecularly doped films at a similar doping level, which suffer from low mobility. Efficient molecular doping should therefore aim for reduced disorder, high doping levels and backbones that favour bipolaron formation.